The potential of cassava leaves extract in gingival fibroblasts of periodontitis of rats with ovarian dysfunction - Shita, Amandia Dewi Permana; Meilawaty, Zahara; Rothschildi, Dhesyarmani Putri; Dharmayanti, Agustin Wulan Suci; Hamzah, Zahreni (Universitas Padjadjaran, 2021)
Introduction: The prevalence of periodontitis has reached 42.8% in Indonesia. One contributing factor is Porphyromonas gingivalis. The ovarian dysfunction caused by ovariectomy procedures may also cause periodontitis. Post ovariectomy conditions resemble menopause, lowering the production of estrogen and progesterone hormones, leaving patients vulnerable to periodontitis. To prevent the side effects of the treatment, herbal ingredients are commonly used. The extract of cassava leaves is known to have pharmacological effects as an antioxidant and, thus, can be applied as a medicine for periodontitis. Methods: A total of 21 rats were divided into three groups, (1) control: healthy rats; (2) Group P.1: P. gingivalis-induced rats; (3) Group P.2: ovariectomized rats. Groups P.1 and P.2 were further divided into three subgroups that were administered cassava leaves extract at a dosage of 179.2 mg/ kg BW, aquades and vitamin C. Rats were euthanized at day eight after the initial treatment to collect left mandibular first molar. The mandibular sections were immunohistochemically stained to quantify SOD expression using light microscope while the Image J software was used. Fibroblast cells expressing SOD are characterized by brown coloration in the cytoplasm and darker nucleus. Results: In periodontitis conditions, either due to P.gingivalis induction or ovarian dysfunction, fibroblast cells in rats given cassava leaves extract expressed higher SOD than rats given aquades, but still lower than rats given vitamin C. The result of the one way ANOVA test showed p value of 0,00, which means that there is a significant difference in all groups. Conclusion: Cassava leaves extract demonstrated the potential to increase the antioxidant expression in P. gingivalis-induced and ovarian dysfunction rats.